2017
DOI: 10.1038/s41598-017-08117-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Suicide Risk in Germany: A Longitudinal Study 2007–11

Abstract: Despite comprehensive prevention programs in Germany, suicide has been on the rise again since 2007. The underlying reasons and spatiotemporal risk patterns are poorly understood. We assessed the spatiotemporal risk of suicide per district attributable to multiple risk and protective factors longitudinally for the period 2007–11. Bayesian space–time regression models were fitted. The nationwide temporal trend showed an increase in relative risk (RR) of dying from suicide (RR 1.008, 95% credibility intervals (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…Data were aggregated across years (2004)(2005)(2006)(2007)(2008)(2009)(2010) to ensure for a sufficient number of suicides in small areas. Any changes in the spatial patterning of suicide during the study period were not considered, and this may be further investigated using space-time models in future research (Helbich et al, 2017b).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Data were aggregated across years (2004)(2005)(2006)(2007)(2008)(2009)(2010) to ensure for a sufficient number of suicides in small areas. Any changes in the spatial patterning of suicide during the study period were not considered, and this may be further investigated using space-time models in future research (Helbich et al, 2017b).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Reducing mental health disparities between urban and rural settings is receiving considerable attention in both scientific and policy debates [ 1 – 4 ], as is suicide mortality [ 5 9 ]. In industrialized nations, suicide is a major cause of death [ 10 ], whereas suicide rates vary greatly across regions [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the living environment also seems to have neurobiological effects that contribute to differences in psychiatric illness [ 18 ], research has also found that urbanity/rurality shapes intra-regional differences in suicide [ 12 , 14 , 19 26 ]. There are many possible explanations for an increased suicide risk in rural areas [ 9 , 12 , 14 , 20 , 26 , 27 ]. For instance, despite popular clichés about anonymous city-dwelling, rural living can lead to social isolation, resulting in less intimate face-to-face contact with family and friends, which, in turn, increases the risk for suicidal behavior [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations